Water Absorption Kinetics in Natural Rubber Composites Reinforced with Natural Fibers Processed by Electron Beam Irradiation - Manaila, Elena (Polymers (Basel), 2020)
Natural rubber composites reinforced with hemp, flax, and wood sawdust were obtained by irradiation at room temperature with an electron beam of 5.5 MeV in order to meet the actual need for new materials that are environmentally friendly and safe for human health. The natural fibers loading was between 5 and 20 phr and the processing doses were between 75 and 600 kGy. The kinetics of water absorption in these materials were studied. The water diffusion was analyzed through Fick’s law. The water absorption parameters (Qt and Qeq), diffusion parameters (k and n), diffusion coefficient (D), intrinsic diffusion coefficient (D*), sorption coefficient (S), and permeation coefficient (P) have depended on the fiber nature, amount used in blends, and irradiation dose. The obtained results showed that not in the case of each type of fiber used, the water absorption could be correlated with the specific cellulose and hemicellulose content, due to the changes induced by the electron beam.